Plume-Induced Subduction Initiation: Revisiting Models and Observations - Baes, Marzieh; Stern, Robert J.; Whattam, Scott; Gerya, Taras V.; Sobolev, Stephan V. (Frontiers in Earth Science, 2021)
Subduction initiation induced by a hot and buoyant mantle plume head is unique among proposed subduction initiation mechanisms because it does not require pre-existing weak zones or other forces for lithospheric collapse. Since recognition of the first evidence of subduction nucleation induced by a mantle plume in the Late Cretaceous Caribbean realm, the number of studies focusing on other natural examples has grown. Here, we review numerical and physical modeling and geological-geochemical studies which have been carried out thus far to investigate onset of a new subduction zone caused by impingement of a mantle plume head. As geological-geochemical data suggests that plume-lithosphere interactions have long been important - spanning from the Archean to the present - modeling studies provide valuable information on the spatial and temporal variations in lithospheric deformation induced by these interactions. Numerical and physical modeling studies, ranging from regional to global scales, illustrate the key role of plume buoyancy, lithospheric strength and magmatic weakening above the plume head on plume-lithosphere interactions. Lithospheric/crustal heterogeneities, pre-existing lithospheric weak zones and external compressional/extensional forces may also change the deformation regime caused by plume-lithosphere interaction.